2002
DOI: 10.1051/0004-6361:20020375
|View full text |Cite
|
Sign up to set email alerts
|

Oscillations above sunspots: Evidence for propagating waves?

Abstract: Abstract. We present results of an analysis of time series data observed in sunspot umbral regions. The data were obtained in the context of the SOHO Joint Observing Program (JOP) 97 in September 2000. This JOP included the Coronal Diagnostic Spectrometer (CDS) and the Michelson Doppler Imaging (MDI) instrument, both part of SOHO, the TRACE satellite and various ground based observatories. The data was analysed by using both Fourier and wavelet time series analysis techniques. We find that oscillations are pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
63
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 32 publications
8
63
0
Order By: Relevance
“…Results similar to the observations by Centeno et al (2006) were produced, as well as normalized amplitudes of a few percent in the transition region (McEwan & De Moortel 2006) that are larger than those in the corona (O'Shea et al 2002). The results demonstrate that three-minute oscillations in the chromospheric cavity are obtained without the need for a clear three-minute source in the photosphere.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Results similar to the observations by Centeno et al (2006) were produced, as well as normalized amplitudes of a few percent in the transition region (McEwan & De Moortel 2006) that are larger than those in the corona (O'Shea et al 2002). The results demonstrate that three-minute oscillations in the chromospheric cavity are obtained without the need for a clear three-minute source in the photosphere.…”
Section: Discussionsupporting
confidence: 81%
“…As one moves higher up in the chromospheric cavity, the oscillation amplitudes increase so that amplitudes are largest at the top of the chromosphere (2.2 Mm). This numerical result agrees with observations that relative oscillation amplitudes reach a maximum in the transition region, decrease with height up till a coronal temperature of 10 6 K, before increasing again as one moves to higher coronal temperatures (O'Shea et al 2002).…”
Section: Oscillations In the Chromospheric Cavitysupporting
confidence: 91%
“…These oscillations are much more prominent in the blue wing of the emission lines than in the red wing (Brynildsen et al 2003). Umbral oscillations with periods between 112 s and 185 s could be seen with CDS and TRACE inside and outside of sunspot plumes; in some cases different frequencies have been observed cospatially and simultaneously (O'Shea et al 2002).…”
Section: Sunspots and Sunspot Plumesmentioning
confidence: 93%
“…Using a combination of different instruments, a number of authors have recently found evidence for the propagation of slow magneto-acoustic waves through the transition region and into the corona. Using mainly CDS/SOHO, MDI/SOHO and TRACE, O'Shea et al (2002) found oscillations present in a sunspot umbra at all investigated temperatures, from the temperature minimum (TRACE 1700 passband) to the coronal temperature of log T = 6.4 (CDS FE XVI 335 Å). The measured propagation speeds suggest that the observed oscillations are slow magneto-acoustic waves propagating from the footpoints along the magnetic field lines.…”
Section: Introductionmentioning
confidence: 91%